Analisis Penyajian Laporan Keuangan Pada Paroki Katedral St. Yoseph Maumere Berdasarkan Isak 35 - Thereza Indariani Peni Ndo; Wihelmina Mitan; Emilianus Eo Kutu Goo (Universitas 45 Surabaya, 2023)
This study aims to determine the presentation of existing financial reports and also to know the presentation of financial reports at St.Yoseph Maumere Cathedral Parish based on ISAK 35. The method used is a type of qualitative research. The research data was obtained from the financial reports of St.Yoseph Maumere Cathedral Parish. Sources of data using primary data and secondary data collected by researchers using interviews, observation and documentation. In data analysis techniques, it has gone through the process of data collection, data reduction, data presentation and drawing conclusions. The research stages used the pre-field stage, the field work stage, the data analysis stage, and the report writing stage. The results of this study indicate that St.Yoseph Maumere Cathedral Parish has implemented the presentation of financial statements in the form of cash in and cash out. The presentation of financial reports based on the interpretation of accounting standards according to ISAK 35 at St.Yoseph Maumere Cathedral Parish has not been implemented due to a lack of knowledge and ability to apply an accounting system according to ISAK 35.